Regioisomerism in Thienothiophene-Based Covalent Organic Frameworks─A Tool for Band-Gap Engineering - Guntermann, Roman; Frey, Laura; Biewald, Alexander; Hartschuh, Achim; Clark, Timothy; Bein, Thomas; Medina, Dana D. (Journal of the American Chemical Society, 2024)
The craft of tuning optical properties is well-established for crystalline inorganic and hybrid solids. However, a far greater challenge is to tune the optical properties of organic materials systematically by design. We now introduce a synthesis concept that enables us to alter the optical properties of crystalline covalent organic frameworks (COFs) systematically using isomeric structures of thienothiophene-based building blocks (T23/32T) combined with a variety of tetratopic aromatic amines, e.g., the Wurster moiety (W-NH2). This concept is demonstrated for the synthesis of COFs in bulk and film forms and provides highly crystalline and porous isomeric COFs featuring predesigned photophysical properties. The band gap of the framework can be tuned continuously and precisely by chemically doping the pristine W23TT COF with its related constitutional isomer building block. Density-functional theory investigations of COF model compounds indicate that the extent of π-conjugation is among the key characteristics enabling the band-gap engineering.
CRIS-Team Scopus Importer:2024-06-14